(untitled) - Wentz, Charles A (Boston, Massachusetts, 1998)
This comprehensive textbook integrates scientific and engineering principles with legislation, regulation, technology, and business. In addition, in-depth coverage of hazard characterization, assessment, prevention, and control are also provided. With the principal safety and health hazards identified, this text satisfies the new ABET requirements for safety, health, and environmental training.
Keywords: Industrial hygiene,Industrial safety